Restorative Justice sebagai Manifestasi Tujuan Hukum: Kajian Filsafat Hukum Wilayah Kejaksaan Tinggi Jawa Tengah - Dwinanda Linchia Levi Heningdyah Nikolas Kusumawardhani (Criminal Law Section Faculty of Law Universitas Sebelas Maret, 2025)
Restorative justice is a legal approach that focuses on restoring the situation and balance between the perpetrators, victims, and the community, as an alternative to the retributive criminal justice system. In the context of legal objectives, certainty, justice, and usefulness, this approach is a tangible manifestation of the progressive legal paradigm. This study examines the implementation of restorative justice within the scope of the Central Java High Prosecutor's Office through the perspective of the philosophy of legal science, by examining how this approach reflects the values of substantive justice and the principles of responsive law This research emphasizes that the concept of restorative justice within the framework of the philosophy of law is able to provide alternative legal solutions that are more humanist and oriented towards social justice. Therefore, it is necessary to strengthen regulations and synergy between law enforcement officials and the public to optimize the effectiveness of this approach in the criminal justice system in Indonesia.